Tissue tropism and optimization and evaluation of diagnostics test for the detection of Pilchard orthomyxovirus (POMV) in Atlantic salmon (Salmo salar) - Tengesdal, Hedda Kjølleberg (The University of Bergen, 2020)
Since 2012, pilchard orthomyxovirus (POMV) has been of major concern to the Tasmanian salmonid industry. The virus was first discovered in pilchards, and is, so far, only shown to be highly infectious to Atlantic salmon (Salmo salar). Salmonid orthomyxovirus necrosis (SON) is caused by POMV and is associated with multisystemic pathology causing high mortalities in the marine phase. The aims of this study were to investigate the tissue tropism and to develop a new diagnostic test to improve early detection of POMV in Atlantic salmon. For this, tissue samples of sub-clinical smolt from a cohabitation challenge were examined. POMV was detected, post injection, in all six tissues examined with a peak of infection between 8- and 12-days in all organs of sub-clinical fish with the exception of the gills which presented high viral loads past this point. Head kidney and heart were the first sites to show presence of POMV in sub-clinical fish, two days post injection, and were also among the tissues with highest viral loads throughout the time course of the experiment. This knowledge revealed that these tissues are effective samples for POMV detection. RT-qPCR assays targeting segment 7 and 8 of the genome of POMV were designed and validated in several steps. However, the improved diagnostic sensitivity of the assays compared to the currently used RT-qPCR assay targeting segment 5, especially for the segment 8 assay, will be of particularly importance to contribute to earlier detection of the virus. Development of an improved diagnostic tool for early detection of POMV is of importance and will allow management of disease at earlier phases, improve animal welfare, and potentially reduce prevalence, transmission and losses due to the virus. Masteroppgave i fiskehelse FISK399 MAMN-FISK